Nexus of Comprehensive Green Innovation, Environmental Management System-14001-2015 and Firm Performance - Parvez Alam Khan (Taylor & Francis Group, 2019)
The massive influx of global warming, pollution, natural resource depletion, waste, wastewater, climate change, and loss of biodiversity are the primary sources of motivating firms to innovate within their businesses. This has caused great concern for academicians, policymakers and practitioners to find solutions in dealing with the environmental issues. To provide the answer to the exiting challenges this study propounds the conceptual framework that explores the intervention of the new amendment in environment management system (14001–2015) towards innovation, comprehensive green innovation, and firm performance. Therefore, the main objective of this study is to find out the role and effect of ISO14001-(2015) on general innovation and comprehensive green innovation. This study combined the institutional theory, (environmental management system) resource-based theory (general innovation, comprehensive green innovation) and stakeholder theory (firm performance) to maximise the resources utilisation though newly amended EMS14001-2015 to meet the stakeholders demands without compromising the ecological standards. The proposed conceptual framework will provide a holistic view of the firm in formulating strategies and implementing a comprehensive green innovation to the industry. Implementation of a comprehensive green innovation will enable businesses to reduce the cost of production and end life cycle impact of the product, process, service and organisational innovation on the environment. By considering the end life cycle of innovation, including minimisation of the resource consumption, waste, waste to water and emission which will create a sustainable competitive advantage for the firm. All in all, this study propounds the conceptual framework of a comparative study between nomal innovation, comprehensive green innovation and organisation performance with the moderation of environmental management system (14001–2015).